Measuring the impact: An assessment of progress in Early Childhood Education, Care and Development in the Caribbean - Charles, Leon (Office of the UNESCO Representative in the Caribbean, 1999)
The data for this monograph were generated from a literature search and a survey of the early childhood sector in 19 countries. It was found that: 1) there is lack of systematic data collection and analysis—only seven countries submitted usable data; 2) systematic sectorial management is new to the region; many countries are moving in that direction with participation from stakeholders; 3) formal legal frameworks are new and exist in six countries; and 4) gross enrolment ratios (GERs) are low, with the maximum for day care being 33 percent. Preschool GERs are short of their 100 percent target, except in the Turks and Caicos Islands. It is recommended that governments should pay more attention to the sector, and that planners should give urgent consideration to establishing data collection systems that would assist management of the sector.
Measuring the impact: An assessment of the progress made in achieving the objectives of the Education for All: Assessment 2000 process as related to Early Childhood Education, Care and Development in the Caribbean
Series Editor: Lynda Quamina-Aiyejina
Keywords: Early childhood care and education